A complication of micropuncture catheter fracture during StarClose re-puncture and review of the literature - Ravi Masson, MD; Charles Sineri, DO; Edwin Cheung, MD; John Reilly, MD; David Landau, MD; On Chen, MD (Journal of Vascular Surgery Cases and Innovative Techniques, 2025)
Permanent vascular closure systems are commonly used for achieving hemostasis after transfemoral percutaneous procedures. However, there exists conflicting data regarding the safety of re-puncturing these devices during subsequent procedures. Because percutaneous procedures have become more prevalent, so have the use of vascular closure devices, emphasizing the need to understand their limitations. The following case report describes a situation where a micropuncture catheter fractured within a closure device during inadvertent repeat device access and the challenges encountered with its retrieval.